Shortcomings in use of data on official development assistance - Francisco, P.; Moreira, S. (Review of Development Finance, 2022)
Official Development Assistance (ODA), or foreign aid, is one of the most important sources of development finance, a situation that could be underpinned by the pandemic and the invasion of Ukraine. The use of data on ODA is widespread in either academic work, governments’ planning or public discourse. This paper points out that the use of such data should take into consideration a number of relevant shortcomings of the underlying concept of ODA. The way that ODA is defined, which has recently been subject to significant changes, can decisively influence the way that its impact on recipients is appraised.